Social Support for Changing Multiple Behaviors: Factors Associated With Seeking Support and the Impact of Offered Support. (April 2018) - Greaney, Mary L.; Puleo, Elaine; Sprunck-Harrild, Kim; Haines, Jess; Houghton, Serena C.; Emmons, Karen M.
Introduction . Social support is important for behavior change, and it may be particularly important for the complexities of changing multiple risk behaviors (MRB). Research is needed to determine if participants in an MRB intervention can be encouraged to activate their social network to aid their change efforts. Methods . Healthy Directions 2, a cluster-randomized controlled trial of an intervention conducted in two urban health centers, targeted five behaviors (physical activity, fruit and vegetable intake, red meat consumption, multivitamin use, and smoking). The self-guided intervention emphasized changing MRB simultaneously, focused on self-monitoring and action planning, and encouraged participants to seek support from social network members. An MRB score was calculated for each participant, with one point being assigned for each behavioral recommendation that was not met. Analyses were conducted to identify demographic and social contextual factors (e.g., interpersonal, neighborhood, and organizational resources) associated with seeking support and to determine if type and frequency of offered support were associated with changes in MRB score. Results . Half (49.6%) of participants identified a support person. Interpersonal resources were the only contextual factor that predicted engagement of a support person. Compared to individuals who did not seek support, those who identified one support person had 61% greater reduction in MRB score, and participants identifying multiple support persons had 100% greater reduction. Conclusion . Engagement of one's social network leads to significantly greater change across multiple risk behaviors. Future research should explore strategies to address support need for individuals with limited interpersonal resources.